Strategi bisnis start up menjaga stabilitas bisnis start up melalui manajemen risiko yang efektif - Ibad, Khairul (Maliki Interdisciplinary Journal, 2025)
Startups are a type of business that is vulnerable to market dynamics and high business risks. To ensure operational continuity and stability, a strategic approach is needed that includes the implementation of comprehensive risk management. Through a systematic process of identifying and handling risks, startups can minimize the negative impacts of various disruptions that arise, such as markets, policy changes, and other operational obstacles. This paper reviews how the integration of business strategy and risk management can provide added value in maintaining business stability. In this way, startups are not only able to survive, but also build a strong foundation to grow sustainably and competitively in the market.